2018
DOI: 10.1177/1054773818791085
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Staff Debriefing Following Seclusion or Restraint Use in Inpatient Mental Health Settings: A Scoping Review

Abstract: The aim of this scoping review is to synthesize the academic and gray literature on the use of immediate staff debriefing following seclusion or restraint events in inpatient mental health settings. Multiple electronic databases were searched to identify literature on the topic of immediate staff debriefing. The analysis identified several core components of immediate staff debriefing: terminology, type, critical reflection, iterative process, training, documentation, and monitoring. While these components wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 73 publications
(151 reference statements)
4
19
0
Order By: Relevance
“…Care providers' experiences and views on PIRs' potential for emotional and relational processing are in line with previous studies that suggest PIRs help the care providers' deal with emotional and moral stress [10,11,13,49]. As PIRs with the patient mainly focus on the patients' experiences and considerations, care providers' personal needs for defusing after restraint events belongs to other arenas [1,11,51]. From patients' perspectives, we have in our review [11] found one small study suggesting PIRs are beneficial regarding patients' processing of the restraint incident [47].…”
Section: Discussionsupporting
confidence: 82%
“…Care providers' experiences and views on PIRs' potential for emotional and relational processing are in line with previous studies that suggest PIRs help the care providers' deal with emotional and moral stress [10,11,13,49]. As PIRs with the patient mainly focus on the patients' experiences and considerations, care providers' personal needs for defusing after restraint events belongs to other arenas [1,11,51]. From patients' perspectives, we have in our review [11] found one small study suggesting PIRs are beneficial regarding patients' processing of the restraint incident [47].…”
Section: Discussionsupporting
confidence: 82%
“…Most participants discussed the need for trauma-informed debriefing. This finding is supported by a scoping review finding a beneficial effect of debriefing immediately following critical events such as implementing seclusion or restraint of a patient during violent behavior (Mangaoil et al, 2018). Formal support programs, including immediate debriefing following violent incidents, would support staff and their feeling of safety (Edward et al, 2016).…”
Section: Service Gapsmentioning
confidence: 92%
“…A scoping review of post‐restraint de‐briefing found little consistency of implementation of de‐briefing in practice (Mangaoil et al . 2018). De‐briefing for staff and service users is considered important because physical restraint can re‐awaken previous traumatic events (Bonner 2007).…”
Section: Introductionmentioning
confidence: 99%